2015
DOI: 10.3102/0034654314550046
|View full text |Cite
|
Sign up to set email alerts
|

Educational Leaders and Emotions

Abstract: The aim of the present article is to review the international evidence about emotional aspects related to educational leaders. The review focuses on empirical studies published in peer-refereed educational journals between 1992 and 2012. First, we address the importance of researching emotions for understanding educational leaders. Next, we present the method used in the production of this narrative review. The bulk of the article presents empirical evidence from 49 studies organized along themes. Three centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
20

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(79 citation statements)
references
References 128 publications
1
58
0
20
Order By: Relevance
“…Some studies (Jennings, 2011;Sutton & Wheatley, 2003) showed the close relation between teachers' socio-emotional skills and their effectiveness and quality during teaching and learning processes in the classroom. The research shows that adequate levels of emotional intelligence help teachers to cope with the problems they face in the educational context more successfully (Berkovich & Eyal, 2015;Ju, Lan, Li, Feng, & You, 2015;Wurf & Croft-Piggin, 2015;Yin, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Some studies (Jennings, 2011;Sutton & Wheatley, 2003) showed the close relation between teachers' socio-emotional skills and their effectiveness and quality during teaching and learning processes in the classroom. The research shows that adequate levels of emotional intelligence help teachers to cope with the problems they face in the educational context more successfully (Berkovich & Eyal, 2015;Ju, Lan, Li, Feng, & You, 2015;Wurf & Croft-Piggin, 2015;Yin, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Following the suggestion that future research should explore the relationship between emotional labor strategies, leadership styles and followers' well-being, work attitudes, and job performance in various contexts (Hülsheger and Schewe, 2011;Berkovich and Eyal, 2015), this study explored the effects of PL on teachers' emotional labor and organizational outcomes. In terms of organizational outcomes, this study selected teacher commitment, which is frequently reported as an important indicator for school effectiveness (Firestone and Pennell, 1993;Park, 2005;Meyer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The head teachers spoke with passion, underpinned by shared core values. Whereas the admission of feelings and sensitivity would previously have been stigmatised (Berkovich and Eyal, 2015), as would the admission of flaws; emotion, fallibility and a willingness to learn from others were very much at the forefront of discussions during this research.…”
Section: Discussionmentioning
confidence: 98%